2013
DOI: 10.1002/hep.26151
|View full text |Cite
|
Sign up to set email alerts
|

Circulating stem cell–like epithelial cell adhesion molecule–positive tumor cells indicate poor prognosis of hepatocellular carcinoma after curative resection

Abstract: Epithelial cell adhesion molecule-positive (EpCAM 1 ) hepatocellular carcinoma (HCC) cells may constitute a tumor-initiating subpopulation in tumorigenic cell lines and HCC specimens. In the present study, EpCAM 1 circulating tumor cells (CTCs) were identified prospectively in HCC patients undergoing curative resection, and the prognostic significance and their stem cell-like characteristics were investigated further. Blood samples from 123 HCC patients were tested prior to resection and 1 month thereafter. CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
335
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 358 publications
(354 citation statements)
references
References 35 publications
16
335
3
Order By: Relevance
“…In the present study, the results of a xenograft assay demonstrated that the CTCs and CTM detected in the PV blood of patients were tumorigenic. Similar human CTC-derived xenograft models have been reported for breast cancer, hepatocellular carcinoma and SCLC (25)(26)(27). In addition, CTC culture has been established successfully from patients with early-stage NSCLC (28).…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, the results of a xenograft assay demonstrated that the CTCs and CTM detected in the PV blood of patients were tumorigenic. Similar human CTC-derived xenograft models have been reported for breast cancer, hepatocellular carcinoma and SCLC (25)(26)(27). In addition, CTC culture has been established successfully from patients with early-stage NSCLC (28).…”
Section: Discussionmentioning
confidence: 65%
“…The entrance criteria were: (i) definitive pathologic or radiologic diagnosis according to American Association for Study of Liver Disease guidelines; (ii) no extrahepatic metastasis at the time of diagnosis; (iii) no prior anticancer treatment (14). Tumor stage was determined according the Barcelona Clinic Liver Cancer (BCLC) staging system, and tumor differentiation was defined according to the Edmondson grading system.…”
Section: Patients and Specimensmentioning
confidence: 99%
“…The criteria for an EpCAM-positive object to be identified as a CTC were nucleated (DAPI þ ) intact cell, positive for pan-cytokeratin 8,18,19, and negative for CD45 (14). To prevent false assignment of a mitotic CTC as a microembolus, circulating tumor microemboli (CTM) was defined as clusters of CTCs containing three or more distinct nuclei (19).…”
Section: Ctc Enumeration and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations